Review Of The Fund's Policy On Multiple Currency Practices : Initial Considerations. - International Monetary Fund. Legal Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper reviews the Fund's policy on multiple currency practices (MCPs). There remain strong economic and legal reasons to retain a policy on MCPs. The over-arching aim of the review is to make the policy and its application more effective. Based on this review, the paper proposes initial considerations for reforming features of the policy that have created challenges. -- Clarifying the concept of 'official action' to focus on measures that segment FX markets. -- Eliminating potentiality. -- Updating the threshold for permissible FX spreads. -- Adjusting approval policies. -- Reviewing links with capital transactions. -- Considering merits of a remedial framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet